2016
DOI: 10.1002/ijc.30037
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent chemotherapy efficacy against leukemia in mice treated with topical vasoconstrictors to prevent cancer therapy side effects

Abstract: Topically applied vasoconstrictor is a new strategy to prevent oral mucositis and alopecia, two complications of chemotherapy and stem-cell transplant. We sought to determine whether mice treated with topical vasoconstrictor minutes before chemotherapy to suppress L1210 leukemia would develop a vasoconstrictor-induced L1210 cell sanctuary, and with it, significantly worse survival outcomes. B6D2F1 mice received 10 4 mouse L1210 leukemia cells via retro-orbital intravenous injection and were then divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The use of oral cryotherapy to reduce OM severity [20] is in itself an acknowledgement of the oral vasoconstriction strategy, and the observed absence of tumor protection with oral cryotherapy [21] as measured by five-year tumor recurrence rates, supports oral mucosal vasoconstriction as a general protective strategy. An earlier report from our laboratory [13] also showed no radiation protection of three, histologically diverse, xenograft, tumor populations that received direct topical application of phenylephrine, epinephrine or norepinephrine 15 minutes before receiving tumoricidal irradiation. This outcome was consistent with the historical observation that human tumor vasculature lacks the smooth muscle cells with adrenergic receptors that are required to enable a response to an adrenergic vasoconstrictor.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The use of oral cryotherapy to reduce OM severity [20] is in itself an acknowledgement of the oral vasoconstriction strategy, and the observed absence of tumor protection with oral cryotherapy [21] as measured by five-year tumor recurrence rates, supports oral mucosal vasoconstriction as a general protective strategy. An earlier report from our laboratory [13] also showed no radiation protection of three, histologically diverse, xenograft, tumor populations that received direct topical application of phenylephrine, epinephrine or norepinephrine 15 minutes before receiving tumoricidal irradiation. This outcome was consistent with the historical observation that human tumor vasculature lacks the smooth muscle cells with adrenergic receptors that are required to enable a response to an adrenergic vasoconstrictor.…”
Section: Discussionmentioning
confidence: 87%
“…The efficacy of a topically applied vasoconstrictor can be visually observed by the “blanching” of mucosa or skin that occurs when oxygenated red blood (as well as any blood-borne chemotherapy it contains) is excluded from the ~1 mm deep layer of mucosa or skin which: i) lies above the submucosal/ subcutaneous vasculature, and ii) contains the mucosal, epidermal, or hair follicle “stem” cells, whose radiation- or chemotherapy-induced apoptosis initiates the oral mucositis, radiation dermatitis or alopecia side effects observed in cancer patients. The transient hypoxia of the surface oral or epidermal stem cells following topical application of vasoconstrictor, or the transient excluded delivery of systemic chemotherapy to oral/epidermal surface stem cells [13] is seen as a logical mechanism to confer chemo- and radio-protection to surface cells while not impeding killing of underlying leukemia [13] or solid tumor cells [14]. The topical vasoconstrictor approach provides both: i) flexibility in the duration of the protective effect and ii) absence of the discomfort associated with oral or scalp cryotherapy [15].…”
Section: Introductionmentioning
confidence: 99%
“…While these results were the first to show the benefit of dynamic control to chemotherapy in a regional perfusion model, phenylephrine and other vasoactive agents have been shown to augment anticancer treatments in other settings [34][35][36] . Preclinical studies of intratumoral epinephrine and fluorouracil in a mouse sarcoma model reported superior responses with this combination compared to fluorouracil alone 37 .…”
Section: Discussionmentioning
confidence: 93%
“…Local injection of phenylephrine has also previously been investigated and found to enhance anticancer treatments. 51,52 For example, one preclinical study of intratumoral epinephrine and fluorouracil in a mouse model of sarcoma demonstrated superior responses with this combination compared to fluorouracil alone. 53 In addition, intratumoral phenylephrine and other vasoactive agents combined with chemotherapy have been used for the treatment of cutaneous head and neck SCC, which also demonstrated significant local tumor responses.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Local injection of phenylephrine has also previously been investigated and found to enhance anticancer treatments. , For example, one preclinical study of intratumoral epinephrine and fluorouracil in a mouse model of sarcoma demonstrated superior responses with this combination compared to fluorouracil alone . In addition, intratumoral phenylephrine and other vasoactive agents combined with chemotherapy have been used for the treatment of cutaneous head and neck SCC, which also demonstrated significant local tumor responses. Phase 3 clinical trials have validated the use of injectable vasoactive gels combined with intratumoral chemotherapy for SCC as well. , Similar to our preclinical animal results, patients who achieved partial or complete pathologic responses in these clinical trials were more likely to have smaller tumors, suggesting that the growth kinetics of the tumor may impact the success of intratumoral therapy.…”
Section: Discussionmentioning
confidence: 99%